Giving Children Control: Fourth Graders Initiate and Sustain Discussions After Teacher Read-alouds - Zoe Donoahue (Networks: An Online Journal for Teacher Research, 1998)
I have always allowed ample time for discussion after reading to the class, believing that it helps children to better understand the text on a basic level, as well as encouraging them to examine characters and their motivations, make predictions, discuss the author's style and choices and explore the characteristics of various genres of writing. The discussions were conducted in what is likely a typical manner: children would raise their hands if they had something to say and I would choose at random, trying to ensure that I gave as many as possible a chance to talk. The effect of these practices was to focus the children's attention on me between every speaker. I was in control of the discussion.